Case Report: Acute Renal and Splenic Infarctions Secondary to Atrial Fibrillation - Yihan, Li; Guanqi, Fan; Tong, Hu; Junye, Ge; Zhong, Jingquan; Chen, Tongshuai (Frontiers in Cardiovascular Medicine, 2022)
Acute renal and splenic infarctions are an uncommon condition that can result from obstruction or decrease of renal and splenic arterial flow. We described a 73-year-old woman presented with right flank pain and nocturnal dyspnea. The computed tomography scan with intravenous contrast showed multiple infarcts in both bilateral kidneys and spleen. Serum creatinine clearance was impaired. Further investigation by electrocardiogram (ECG) and 24-hour Holter revealed that the patient had paroxysmal atrial fibrillation (PAF). Transthoracic and transesophageal echocardiographic findings were unremarkable except for severe spontaneous echo contrast (SEC) in the left atrial appendage. Development of thromboembolic renal and splenic infarction was attributed to embolism caused by atrial fibrillation. Anticoagulant therapy was initiated with low molecular weight heparin (LMWH) and followed by oral anticoagulant. In order to manage PAF and prevent further embolism, the "One-stop" procedure including atrial fibrillation catheter ablation and left atrial appendage occlusion (LAAO) was applied to this patient. Follow-up at one month showed normal sinus rhythm, improved renal function and relieved renal and splenic infarction.